2019
DOI: 10.5897/ajar2018.13641
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea (Vigna unguiculata (L.)Walp., Fabaceae) landrace (local farmers varieties) diversity and ethnobotany in Southwestern and Eastern parts of Ethiopia

Abstract: The present research was carried out to identify and document the landrace diversity and ethnobotanical uses of cowpea (Vigna unguiculata (L.) Walp) (Fabaceae) in Southwestern and Eastern Ethiopia. Data were collected through field observations, semi-structured interviews, guided field walk with cowpea farmers and users, and market surveys. Descriptive statistics, preference ranking and informant consensus were employed in the analysis. Forty-four cowpea accessions were collected from geographical locations ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Indeed, the regions of Mayo Kebbi Est and Ouest, present a significant diversity per village. Regionally, the average number of landraces in this part of southern Chad is almost similar to that of three regions located in the southwestern parts of Ethiopia (Alemu et al, 2019). However, the average of landrace collected per village which is 2.70 is low compared to 4.29 reported by Gapili et al (2020).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Indeed, the regions of Mayo Kebbi Est and Ouest, present a significant diversity per village. Regionally, the average number of landraces in this part of southern Chad is almost similar to that of three regions located in the southwestern parts of Ethiopia (Alemu et al, 2019). However, the average of landrace collected per village which is 2.70 is low compared to 4.29 reported by Gapili et al (2020).…”
Section: Discussionsupporting
confidence: 67%
“…In terms of treatments for therapeutic uses, in a study conducted in Togo, Agbodan et al (2020) identified local varieties of cowpea that help to fight against malnutrition because they have remarkable antioxidant potential compared to the introduced varieties. In Ethiopia, the green leaves and grains of cowpea are used in the treatment of liver disease, gastritis and malaria (Alemu, 2019).…”
Section: Research Articlementioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License production complexes are located in the Southern and Western parts of the country (Bedru et al, 2019;Sisay et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity is a prerequisite for the identification of superior genotypes, which may be recommended for direct release as commercial cultivars for wider production, but also for the identification of desirable parents to use as source materials in breeding programs (Rajaravindran and Natarajan, 2011). Ethiopia is believed to have considerable genetic diversity for cowpea both at phenotypic and genotypic levels (Belayneh et al, 2016;Mulugeta et al, 2016;Sisay et al, 2019;Tesfaye et al, 2019). Apart from genetic diversity for the regular morpho-agronomic traits at phenotypic level and for molecular diversity at genotypic level, information on the magnitude and pattern of phenotypic diversity for immature pod traits in Ethiopian landrace collections is scanty.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several ethnobotanical studies have documented the continued use of traditional legume varieties by farmers (e.g. [35,36]), but have not investigated their current status in a systematic way. To date, there has been no nationwide survey to document farmers’ knowledge and use of grain legume varieties.…”
Section: Introductionmentioning
confidence: 99%